Analyzing the Influence of Education Level, Ethnicity, and Their Interaction on Social Integration among Juveniles in Conflict with the Law - Dewi, Annisa Dianesti; Purwandari, Eny; Dianesti, Nadia Puti; Iranda, Agung; Nofrianda, Rion; Nur, Cut Syarifah (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the influence of education level, ethnicity, and their interaction on the social integration of juveniles in conflict with the law. Social integration is a crucial aspect in the rehabilitation process, particularly for adolescents who experience social stigma and marginalization due to their legal status. A total of 260 juveniles in conflict with the law, recruited from Lembaga Pembinaan Khusus Anak (LPKA) across several provinces in Java, Indonesia, participated in this quantitative study. Data were collected using a validated and reliable social integration scale and analyzed using a two-way analysis of variance (ANOVA). The findings indicate that neither education level nor ethnicity independently had a statistically significant effect on social integration. However, a significant interaction effect between education and ethnicity was found. Specifically, juveniles from the Betawi ethnic group with junior high school education exhibited a lower level of social integration compared to their Javanese counterparts. These findings suggest that the combination of socio-educational background and cultural identity may influence the success of social integration among at-risk youth. This study highlights the importance of culturally responsive rehabilitation programs that consider both educational and ethnic factors in promoting social harmony and reintegration.